2009
DOI: 10.1890/08-1346.1
|View full text |Cite
|
Sign up to set email alerts
|

Reliable cues and signals of fruit quality are contingent on the habitat in black elder (Sambucus nigra)

Abstract: Communication mediates interactions between organisms and can be based on signals or cues. Signals are selected for their signaling function, whereas cues evolve for reasons other than signaling. To be evolutionarily stable, communication needs to be reliable on average, but the mechanisms that enforce reliability are hotly debated in light of strong environmental influence on signals and cues. While fruit quality in black elder (Sambucus nigra) is unrelated to fruit color, it is indicated by alternative pedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 54 publications
1
35
1
Order By: Relevance
“…For example, in Sambucus nigra subsp. nigra and Sambucus racemosa, it has been reported that their establishment and fruit production increases in sites with the highest light availability (Atkinson & Atkinson 2002, Abe et al 2008, Schaefer & Braun 2009). These results coincide with what we found in this study, since in micro-environment one, which showed the highest canopy openness as well as light amount, the individuals of S. nigra subsp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Sambucus nigra subsp. nigra and Sambucus racemosa, it has been reported that their establishment and fruit production increases in sites with the highest light availability (Atkinson & Atkinson 2002, Abe et al 2008, Schaefer & Braun 2009). These results coincide with what we found in this study, since in micro-environment one, which showed the highest canopy openness as well as light amount, the individuals of S. nigra subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of fruit color have predominated research on this debate. In the black elder (Sambucus nigra), visual contrasts in the pedicels bearing the fruits are positively associated with sugar content (Schaefer & Braun, 2009). Chromatic and achromatic (brightness) properties of fruits are also sometimes correlated with nutritional content (Cazetta, Galetti, Rezende, & Schaefer, 2012;Valido, Schaefer, & Jordano, 2011).…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that plant signals and cues are critical to fruit selection by animals2345. While ripe fruit signals refer to traits such as colour and odour that are maintained by natural selection because of their ability to reliably convey information to other organisms6, ripe fruit cues refer to traits that evolved in a context unrelated to animal signalling (e.g. red anthocyanine pigmentation), that may nonetheless convey reliable information to dispersers7.…”
mentioning
confidence: 99%
“…Plant signals and cues available to animals depend critically on three complex factors: first, the complete signal being broadcast, second, its arbitration by the local environment6, and third, animal sensory phenotypes, which mediate the detectability of plant signals and cues to potential seed dispersers and pollinators10. Plant signals and cues are highly variable8, and comprise visual components - chromaticity (hue, saturation)11, brightness or luminance12 - and odour components, including individual volatile compounds as well as overall odour plume13.…”
mentioning
confidence: 99%